WADAH PECEL AE: STATISTICAL DATA SERVICE INNOVATION IN THE COVID-19 PANDEMIC - Ivan Erdi Yanuar; Yana Syafriyana Hijri (DIA: Jurnal Administrasi Publik, 2022)
In the context of good governance, innovation in data services by providing integrated statistical services is the main gate of government bureaucratic reform, because the service program is a space where the government bureaucracy interacts directly with the community (Febriananingsih, 2012). As is the case with BPS Madiun regency created an innovative data service in the form of an integrated statistical service with an application called Wadah Pecel AE. This application aims to optimize data services during the COVID-19 pandemic. The Wadah Pecel AE application can be used by users to access data remotely and can be used without using internet access. This integrated statistical service program includes print libraries, digital libraries, statistical consulting, and recommendations for sectoral statistical activities. This study aims to describe the innovation of data publication that has been made by the Central Bureau of Statistics Madiun regency in the era of the covid-19 pandemic. This type of research is qualitative with data collection techniques in the form of observation and interviews. The location of this research is in the Central Bureau of Statistics Madiun regency. The results of the study stated that the Central Bureau of Statistics Madiun regency has run a program of innovations that have been made. The program is the Integrated Statistical Service which has been running optimally. Thus, in the era of the COVID-19 pandemic, it is not an obstacle to providing data services to the public. BPS Madiun regency continues to develop innovations to meet the needs of data users.